Character development strategies through the soft skills training to students for job readiness - Rosidah Rosidah; Nadia Sasmita; Voettie Wisataone; Mochamad Hanafi (Universitas Negeri Yogyakarta, 2022)
Instilling the character values is realized through a learning process that aims to equip graduates with job readiness and help internalize values for student life on campus and in society. This study aims to investigate the effects of giving soft skills training on student character development. The research respondents consisted of 148 students. This study employed a quantitative approach. Primary data were gathered using a questionnaire. The data validity utilized content validity and item validation with product moment Pearson correlation analysis. Data analysis used paired-sample tests. The results show that there was a significant difference in the student’s character before and after obtaining soft skill materials. Student character values are better after being given soft skill training than before getting soft skill training.